Extraction and Purification of Staphylolysin enzyme produced by Pseudomonas aeruginosa - Najim, Shayma'a; Flayyih, May (Iraqi Journal of Science, 2024)
Pseudomonas aeruginosa was isolated from various clinical samples included urine, sputum, stool, ear, wound & burn swabs. Detection of the ability of local isolates to produce staphylolysin enzyme was studied, on Tryptic soya agar + 0.2% (wt./vol.) of heat killed Staphylococcus. aureus at temperature 100oC. medium and the diameters of lysis zone ranged from 5-22mm, then the isolate P16 was chosen to extract staphylolysin A (LasA) and its specific activity reaches 8.59 unit /mg protein, whi1e the isolate P5 was chosen to extract staphylolysin D (LasD) where it's specific activity reaches 0.66 unit /mg protein since the two isolates were the most production of enzyme. Staphylolysin enzyme was extracted by cooling centrifugation and partially purified by ammonium sulphate precipitation in saturation percentage of 80%, this step was followed by Ion exchange chromatography technique by using DEAE- cellulose column, results showed that the enzymatic activity (Staphylolytic activity) of the staphylolysin A appeared in first peak with purification folds and recovery of 10.74 fold and 14.2% respectively, while the second peak appeared the activity for staphylolysin D with purification folds and recovery of 9.1 fold and 18.14% respectively.